2017
DOI: 10.1016/j.watres.2017.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Removal of atrazine and its by-products from water using electrochemical advanced oxidation processes

Abstract: Please cite this article as: Komtchou, S., Dirany, A., Drogui, P., Robert, D., Lafrance, P., Removal of atrazine and its by-products from water using electrochemical advanced oxidation processes, Water Research (2017Research ( ), doi: 10.1016Research ( /j.watres.2017 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(23 citation statements)
references
References 42 publications
(27 reference statements)
0
20
0
Order By: Relevance
“…This phenomenon has also been found in many electrochemical degradation processes of losartan (Salazar et al 2016), sulfamethazine (Barhoumi et al 2016;Sopaj et al 2016), ifosfamide (Fabianśka et al 2015) and nitrobenzene (Rabaaoui et al 2013). The increase of current density resulted in a higher concentration of •OH in the bulk solution (Komtchou et al 2017). In addition, the BDD anode can extend the range of current densities and significantly raise the most optimal current density compared to Pt and DSA anodes based on its very high O 2 evolution over potential and weak adsorption of BDD(•OH) (Sopaj et al 2016).…”
Section: Effects Of Current Density On Dcf Degradationmentioning
confidence: 62%
See 1 more Smart Citation
“…This phenomenon has also been found in many electrochemical degradation processes of losartan (Salazar et al 2016), sulfamethazine (Barhoumi et al 2016;Sopaj et al 2016), ifosfamide (Fabianśka et al 2015) and nitrobenzene (Rabaaoui et al 2013). The increase of current density resulted in a higher concentration of •OH in the bulk solution (Komtchou et al 2017). In addition, the BDD anode can extend the range of current densities and significantly raise the most optimal current density compared to Pt and DSA anodes based on its very high O 2 evolution over potential and weak adsorption of BDD(•OH) (Sopaj et al 2016).…”
Section: Effects Of Current Density On Dcf Degradationmentioning
confidence: 62%
“…Ahn et al (2017) experimentally determined the rate constants NOM affects the oxidation reaction based on radicals through scavenging radicals and reversing the radicals intermediates to the parent compound (Lutze et al 2015;Feng et al 2017). Komtchou et al (2017) also found the HA competed with the containment and its by-products during water treatment. Thus, the inhibited degradation of DCF was expected in this study.…”
Section: Effects Of Electrode Spacing On Dcf Degradationmentioning
confidence: 99%
“…5c). These results point to the raising initial generation of products in the order: desethyl desisopropyl atrazine < cyanuric acid < desethyl atrazine [18].…”
Section: Evolution Of Primary Aromatic Productsmentioning
confidence: 81%
“…Komtchou et al proposed the use of an electrochemically advanced oxidation process from water sample in the elimination of atrazine and its by-products. 27 It was primarily focused on the degradation of atrazine and its by-products using electrochemically advanced oxidation processes, such as anodic-oxidation with simultaneous H 2 O 2 formation (AO-H 2 O 2 ), electro-Fenton (EF), and photoelectro-Fenton (PEF). By comparing these three reactions route, the PEF method was found to be the most effective process for the degradation of atrazine and its byproducts.…”
Section: Detection Methods Of Pesticide Compoundsmentioning
confidence: 99%